Modeling the Trooz Glacier’s movement using air temperature data and satellite SAR observations in 2015‒2022 - Tretyak, K.; Kukhtar, D. (Ukrainian Antarctic Journal, 2023)
The aim of this study is modeling the dependence of maximum velocity of the Trooz Glacier (Kyiv Peninsula, West Antarctica) on air temperature. For this purpose, we processed a time series of meteorological observations at the Akademik Vernadsky station and the ice flow velocity of the Trooz Glacier. The ice velocities were determined from the synthetic aperture radar images, acquired by the Sentinel-1 satellite, for the period from May 2015 to November 2022. The SAR images were processed in the SNAP (Sentinel Application Platform) program using the Offset Tracking method. As a result, 219 ice flow velocity maps were obtained. During the studied period, the maximum velocities varied from 2.64 m/day (August 19, 2015) to 4.05 m/day (April 18, 2020). A functional dependence between the temperature data from the Akademik Vernadsky station and the remotesensing data on the air temperature above the glacier’s surface was established. We combined the three parameters (time series of the maximum velocities of the glacial flow, remote temperature measurements above the glacier, and direct temperature measurements at the Akademik Vernadsky station) in a linear model. In order to increase the accuracy of the modeling, an a posteriori optimization was carried out. As a result, the average error in determining the maximum velocity of the glacier reduced from 23 cm/day to 17 cm/day.